Uncertainty in the manufacturing of fibrous thermosetting composites: A review - Mesogitis, Tassos; Skordos, Alexandros A.; Long, A. C. (Elsevier, 2014)
Composites manufacturing involves many sources of uncertainty associated with material properties variation and boundary conditions variability. In this study, experimental and numerical results concerning the statistical characterization and the influence of inputs variability on the main steps of composites manufacturing including process-induced defects are presented and analysed. Each of the steps of composite manufacturing introduces variability to the subsequent processes, creating strong interdependencies between the process parameters and properties of the final part. The development and implementation of stochastic simulation tools is imperative to quantify process output variabilities and develop optimal process designs in composites manufacturing.
Keywords: Thermosetting resin; Statistical properties/methods; Probabilistic methods